DESIGN AND DEVELOPMENT OF AN AUTOMATED SMART BROODER SYSTEM FOR MINI POULTRY FARMS - Alisher Khamroev (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. Early-stage chick rearing requires controlled environmental conditions to ensure survival, growth, and disease prevention. Manual brooder systems used in small poultry farms often suffer from temperature instability, improper ventilation, and inefficient feeding management. This paper presents the design and implementation of an automated smart brooder system intended for mini poultry farms. The proposed system integrates environmental sensors, microcontroller-based automation, heating regulation, ventilation control, lighting scheduling, and feeding alerts. Experimental evaluation demonstrates improved thermal stability, reduced chick mortality, and decreased human intervention. The developed solution provides a low-cost and scalable approach suitable for rural and small-scale poultry production.